DIRECTIVES IN ENGLISH - F.X. Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1994)
English has many ways of expressing directives. This paper attempts to classify the examples of directives based on their linguistic forms, which then will be given some comments. These comments, despite being subjective, are based on observation and inquiries to native speakers of English. Finally, this paper discusses other possible ways which can be used to classify the directives and the implications for learners and teachers of English to speakers of other languages. Austin (quoted by Coulthard, 1985) makes the distinction between locutionary and illocutionary acts, and he says further that